THE STAGES OF FORMATION OF UZBEK EPOS STUDIES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article provides an in-depth analysis of the formation and developmental stages of Uzbek epic studies as an independent scholarly field. It examines the theoretical views of representatives of the Jadid movement in the early twentieth century, in particular Abdurauf Fitrat and Vadud Mahmud, on epic studies. The article substantiates that Fitrat’s division of literature into “written” and “folk literature,” as well as his introduction of the criterion of “eloquence” in evaluating epics, laid a conceptual foundation for the discipline. Furthermore, it highlights the practical significance of the first folklore expeditions of the 1920s–1930s conducted under the leadership of Go‘zi Olim Yunusov and Hodi Zarifov. These expeditions played a crucial role in preserving the nation’s epic heritage by introducing the methodology of directly recording baxshi performances without alteration. The study also emphasizes that in the period of independence, epic studies have been reinterpreted on the basis of new scholarly criteria—namely, nationality, historicity, and spiritual heritage.